The credibility of speed limits on 80 km/h rural roads: The effects of road and person(ality) characteristics - Goldenbeld, Charles; van Schagen, Ingrid (Accident analysis and prevention, 2007)
The present study aimed to operationalise the concept of credible speed limits and to make a first step to elaborate it in such a way that road authorities can put the concept into practice. The study focused on the credibility of an 80 km/h limit for different rural roads and assessed the effects of characteristics of the road and its environment as well as the effects of person and personality characteristics. Almost 600 Dutch car drivers were asked to judge 27 photographs of (different) rural roads with a posted speed limit of 80 km/h. To determine the degree of credibility, for each road scene the subjects filled in the preferred speed and the speed limit they considered to be safe. The results show large differences in both preferred speed and the safe speed limit between the road scenes, both below and above the limit of 80 km/h. These differences were related to a number of characteristics of the road and the road environment, such as the presence or absence of a curve and characteristics concerning the field of view (sight distance, clarity of situation). There were also large differences between subjects and these were related to age, the degree of sensation seeking, the number of speeding tickets in the last 3 years and the part of the country they lived in. Subjects were influenced by more or less the same road features.